Potential of aquatic fern as carbon sequestration agent to reduce carbon emission in urban ecosystem as an effort to nurture Islamic environmental ethics - Abu Yazid, Anis Fatihah; Othman, Rashidi
The increasing concentration of carbon dioxide emissions markedly in the twentieth century has contributed many negative impacts towards the global conditions. Efforts in reducing carbon dioxide emissions to stabilize atmospheric carbon emission levels have become one of the major concerns globally. The terms carbon footprint, greenhouse effect, urban heat island and many others have become commonly used nowadays when it comes to the negative impacts of climate and major contributor of global warming due to the uncontrolled carbon dioxide emission. Fortunately, studies done on variety of environmental indicator shows that the mentioned issues can be gradually mitigated with suitable implementation of the selected phytoindicators. Fern particularly is known for its environmental indicators quality by many researchers can be greatly utilised for carbon sequestration. Besides its significant values and applications in landscape designs, fern species also possesses the quality as very susceptible environmental indicators to forecast the microclimate changes particularly in urban areas. Due to its high susceptibility towards any subtle and significant changes of its environment, it can be implemented to indicate similar relationships between the environment and also as indicators for the early signs of microclimate changes at different latitude. Generally, fern not only considered as valuable ethno-botany plants that provide food and medicine but also ecologically useful to treat unhealthy environment such as absorbing the methane gas, nourishing the land and to treat heavy metal such as arsenic. Therefore, this paper aims of using environmental indicator for carbon design. Highenergy requirement and cost are the current drawback of carbon mineral sequestration despite of its vast advantages. It is also sequestration at urban areas will be addressed by investigating the selected fern species which is Azolla sp. To further highlight the significant of Azolla sp., we will also explore in details its other potential uses and advantages to be applied later in the current global condition especially in the field of landscape important to investigate the dynamic Azolla-Anabaena relationship to ensure the efficiency of its carbon sequestration process.